Are we free? - edited by John Baer; James C. Kaufman; Roy F. Baumeister (Oxford University Press, 2008)
free will influence behavior? Can free will be studied, verified, and understood scientifically? How and why might a sense of free will have evolved? These are a few of the questions this book attempts to answer